Current status of continuous training of nurses in clinical departments and some influencing factors at Phu Yen General Hospital in the period 2019-2020 (Vietnam Journal of Community Medicine, 2022)
Objectives: The study aims to (1) describe the status of continuous training of nurses in 18 clinical departments and (2) analyze factors affecting associated with the continuous training of nurses in 18 clinical departments, Phu Yen Provincial General Hospital in the period of 2019-2020.Methods: The study design is a descriptive cross-sectional study, combining qualitative and quantitative research conducted through interviews with 198 nurses from clinical departments, 10 in-depth interviews, and 02 discussions. group and secondary data on continuous education (LTLT) for 2 years from 2019 - 2020 at Phu Yen Provincial General Hospital.Results: 48% of the nurses participated in the training for 48 periods/2 consecutive years in accordance with the provision of Circular 22/2013/TT-BYT. 100% of nurses needed to be trained. Lack of human resources, limited funding for continuous training and always overloaded patients are werefactors that negatively affect nursing work. The positive influencing factorwas is that young nurses have high professional qualifications, mainly from college or higher, so the absorption of lectures and application to the care and service of patients in clinical departments has achieved good results.Conclusion: The hospital needs to have a plan to allocate funds and arrange reasonable human resources to participate in teaching and learning to ensure the implementation of the teaching and learning work for 48 consecutive periods/2 years and according to the nurses' needs.
Keywords: Continuous training, nursing in clinical departments.